REVIEW OF METHODOLOGIES FOR EVALUATING UNIVERSITY SOCIAL RESPONSIBILITY - Martí Noguera, Juanjo (2014)
The article presents a review of methodologies for the assessment of the so-called University Social Responsibility from the analysis of indicator systems in the area of higher education in Ibero-America. A publication-based research was conducted, compiling progress made between the years 2006-2013. A total of two doctoral theses that presented evaluation systems in students; two models proposed by universities in Peru and Spain; and the papers of two university networks that designed a University Social Responsibility conceptual development and indicator systems for its assessment were identified. The article points out that despite the spectrum of conceptual proposals produced during the first decade of the 21st century, only a few assessment programs are still in force. This situation is marked as a positive factor to identify strengths and weaknesses in the proposed models, and to allow for a joint development between Ibero-American universities.